Proton-Electron Hole Interactions in Sr(Ti, Fe)O3−δ Mixed-Conducting Perovskites. Issue 5 (1st May 2022) - Miruszewski, T.; Skubida, W.; Winiarz, P.; Dzierzgowski, K.; Mielewczyk-Gryń, A.; Wachowski, S.; Gazda, M.
Abstract : Oxides in which total electrical conductivity is determined by the partial conductivities of three types of charge carriers i.e. holes/electrons, oxygen ions, and protons are key components of well-functioning proton ceramic fuel cells. Apart from electrochemical properties also easily modified microstructure is an important feature of the electrodes. In the paper, a group of SrTi1−x Fex O3− δ (STF, x = 0.2–0.8) perovskites prepared by solid-state synthesis was studied. The microstructure of ceramics was studied using SEM, and the results showed a significant influence of Fe amount on the grain size and material's porosity. The electrical transport results show a different conductivity in a dry and humidified atmosphere. The hydration kinetics related to the water incorporation are presented with the transition from single-fold to two-fold behaviour, related to the proton-electron hole interaction observed in measurements. The obtained results strictly show a triple-conductivity of SrTi0.8 Fe0.2 O3− δ system at a lower temperature range, where the protonic defects are thermodynamically stable.